Borders, Market Size and Urban Growth, The Case of Saxon Towns and the Zollverein in the 19th Century - Florian Ploeckl (Yale University, Economic Growth Center, 2008)
Changes in trade institutions, such as the abolishment of tariff barriers, have a potentially strong impact on economic development. The Zollverein, the 1834 customs union between German states, erased borders in much of central Europe. This paper investigates the Zollverein's economic impact through a study of urban population and its growth in the German state of Saxony. A model of the effect of market access on urban growth is combined with an extensive data set on town populations in Saxony and its neighbors as well as an improved distance measure based on GIS techniques, which take into account elevation patterns, roads, and rivers. The results show that Zollverein membership led to significantly higher growth for towns close to the border with fellow Zollverein member Thuringia. They also illustrate that natural resources affect town size but not the growth pattern after the Zollverein. The effects of changes in market access were reinforced through the impact on market access in other towns and they were stronger for larger towns as well. Migration was the predominant source of the differential growth pattern.
Keywords: F15; N93; R12; 330; Zollverein; saxony; customs union; market access; economic geography; GIS; distance measurement